The Effect of Residual Pesticide Application on Microbiomes of the Storage Mite Tyrophagus putrescentiae - Hubert, Jan; Nesvorna, Marta; Bostlova, Marie; Sopko, Bruno; Green, Stefan J; Phillips, Thomas W (Microbial ecology, 2023)
Arthropods can host well-developed microbial communities, and such microbes can degrade pesticides and confer tolerance to most types of pests. Two cultures of the stored-product mite Tyrophagus putrescentiae, one with a symbiotic microbiome containing Wolbachia and the other without Wolbachia, were compared on pesticide residue (organophosphate: pirimiphos-methyl and pyrethroid: deltamethrin, deltamethrin + piperonyl butoxide)-containing diets. The microbiomes from mite bodies, mite feces and debris from the spent mite diet were analyzed using barcode sequencing. Pesticide tolerance was different among mite cultures and organophosphate and pyrethroid pesticides. The pesticide residues influenced the microbiome composition in both cultures but without any remarkable trend for mite cultures with and without Wolbachia. The most influenced bacterial taxa were Bartonella-like and Bacillus for both cultures and Wolbachia for the culture containing this symbiont. However, there was no direct evidence of any effect of Wolbachia on pesticide tolerance. The high pesticide concentration residues in diets reduced Wolbachia, Bartonella-like and Bacillus in mites of the symbiotic culture. This effect was low for Bartonella-like and Bacillus in the asymbiotic microbiome culture. The results showed that the microbiomes of mites are affected by pesticide residues in the diets, but the effect is not systemic. No actual detoxification effect by the microbiome was observed for the tested pesticides.
Keywords: Bartonella; Pesticides; Pyrethrins; pesticidy; Mites; Pesticide; Mold mite; mikrobiota; Wolbachia; rezidua pesticidů; Microbiota; roztoči; Animals; Bacillus; zvířata; Acaridae; Antibiotics; pyrethriny; Pesticide Residues; Microbiome